2020
DOI: 10.1093/jbcr/iraa003
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Treatment for Partial Thickness Burns: A Cost-Utility Analysis of Skin Allograft vs. Topical Silver Dressings

Abstract: Introduction Partial thickness burns not undergoing surgical excision are treated with topical silver products including silver sulfadiazine (SSD) and Mepilex Ag. Skin allograft is a more costly alternative that acts as definitive wound coverage until autogenous epithelialization. Economic constraints and the movement toward value-based care demand cost and outcome justification prior to adopting more costly products. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Ressaltase que existem variados tratamentos tópicos para as queimaduras, ao passo que as condições do serviço hospitalar e os recursos disponíveis na unidade de queimados devem ser levados em conta, a fim de proporcionar o arsenal terapêutico mais adequado conforme a superfície corporal queimada, o local do corpo atingido pela queimadura e a profundidade da lesão. A ciência segue na busca por um tratamento tópico mais eficiente para as queimaduras, o qual deve apresentar, simultaneamente, atividade antimicrobiana, facilidade para aplicação e controle da dor, além de mínimo custo possível (26). Um estudo encontrou que em 60 dias, 7,9% dos pacientes desenvolveram alguma infecção, sendo que 35,8% atingiram a pele e tecidos moles, 24,4% os pulmões, 18,1% a corrente sanguínea e 17,8% o trato urinário (27).…”
Section: Discussionunclassified
“…Ressaltase que existem variados tratamentos tópicos para as queimaduras, ao passo que as condições do serviço hospitalar e os recursos disponíveis na unidade de queimados devem ser levados em conta, a fim de proporcionar o arsenal terapêutico mais adequado conforme a superfície corporal queimada, o local do corpo atingido pela queimadura e a profundidade da lesão. A ciência segue na busca por um tratamento tópico mais eficiente para as queimaduras, o qual deve apresentar, simultaneamente, atividade antimicrobiana, facilidade para aplicação e controle da dor, além de mínimo custo possível (26). Um estudo encontrou que em 60 dias, 7,9% dos pacientes desenvolveram alguma infecção, sendo que 35,8% atingiram a pele e tecidos moles, 24,4% os pulmões, 18,1% a corrente sanguínea e 17,8% o trato urinário (27).…”
Section: Discussionunclassified
“…In several studies, researchers have demonstrated the superiority of traditional and new-generation allograft compared with products engineered from nonhuman tissue sources. [53][54][55] In other cases, it is impossible to conclude the superiority of a new-generation product that is more expensive than traditional therapeutic alternatives, 56 and health systems must ultimately choose whether to approve the new product.…”
Section: We Recommend That Governments and Policymakers Take All Nece...mentioning
confidence: 99%
“…Cultured epithelial allografts have been used for temporary coverage of acute burns as a bridge to eventual cultured epithelial autografting. Cost-utility analysis suggested that they facilitate healing in partial-thickness burns [78] . Cultured epithelial autografts may speed wound closure when combined with meshed skin grafts [78] .…”
Section: Stem Cells and Other Cellular Therapiesmentioning
confidence: 99%
“…Cost-utility analysis suggested that they facilitate healing in partial-thickness burns [78] . Cultured epithelial autografts may speed wound closure when combined with meshed skin grafts [78] . Fibroblasts added to dermal scaffolds may produce ECM proteins and growth factors that improve healing [77,79] .…”
Section: Stem Cells and Other Cellular Therapiesmentioning
confidence: 99%